(untitled) (ENTHYMEMA, 2010)
Recensiamo il saggio di Ronald D. LeBlanc, Slavic Sins of the Flesh: Food, Sex, and Carnal Appetite in Nineteenth-century Russian fiction, University of New Hampshire Press, Durham, 2009.